Kinetic Analysis of the Thermal Decomposition of Latex Foam according to Thermogravimetric Analysis - Hongwei Fan; Yongliang Chen; Dongmei Huang; Guoqin Wang (International Journal of Polymer Science)
The thermal decomposition of latex foam was investigated under nonisothermal conditions. Pieces of commercial mattress samples were subjected to thermogravimetric analysis (TG) over a heating range from 5°C min−1 to 20°C min−1. The morphology of the latex foam before and after combustion was observed by scanning electron microscopy (SEM), and the primary chemical composition was investigated via infrared spectroscopy (FT-IR). The kinetic mechanism and relevant parameters were calculated. Results indicate that the decomposition of latex foam in the three major degradation phases is controlled by third-order reaction (F3) and by Zhuravlev’s diffusion equation (D5). The mean E values of each phase as calculated according to a single heating rate nonisothermal method are equal to 41.91 ± 0.06 kJ mol−1, 86.32 ± 1.04 kJ mol−1, and 19.53 ± 0.11 kJ mol−1, respectively. Correspondingly, the preexponential factors of each phase are equal to 300.39 s−1, 2355.65 s−1, and 27.90 s−1, respectively. The mean activation energy E and preexponential factor A of latex foam estimated according to multiple heating rates and a nonisothermal method are 92.82 kJ mol−1 and 1.12 × 10−3 s−1, respectively.